2022
DOI: 10.1155/2022/3536108
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Vaginal Microbiota on Spontaneous Preterm Birth among Chinese Pregnant Women

Abstract: Objective. The effect of vaginal microbiota on spontaneous preterm birth (sPTB) has not been fully addressed, and few studies have explored the associations between vaginal taxa and sPTB in the gestational diabetes mellitus (GDM) and non-GDM groups, respectively. Study Design. To minimize external interference, a total of 41 pregnant women with sPTB and 308 controls (pregnant women without sPTB) from same regain were enrolled in this case-cohort study. Controls were randomly selected at baseline. With the exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…Specifically, we reanalyzed data from a study of the vaginal microbiome and preterm birth, and examined the first time point from each of the 40 individuals included in the study 13 ( Methods ). As previously reported 2224 , we observed an association between α diversity and subsequent preterm birth ( Fig. 2a , Mann-Whitney U p = 0.037).…”
Section: Resultssupporting
confidence: 88%
“…Specifically, we reanalyzed data from a study of the vaginal microbiome and preterm birth, and examined the first time point from each of the 40 individuals included in the study 13 ( Methods ). As previously reported 2224 , we observed an association between α diversity and subsequent preterm birth ( Fig. 2a , Mann-Whitney U p = 0.037).…”
Section: Resultssupporting
confidence: 88%
“…This hypothesis has been supported in studies involving white individuals, but further research is needed to determine its applicability to individuals of other groups [16]. In the Hui Kan et al study, the presence or absence of diabetes was included as an influencing factor, and it was found that the risk of spontaneous preterm birth in all women decreased with Lactobacillus mulieris while the risk in gestational diabetics increased with Lactobacillus paragasseri, Lactobacillus gasseri, Streptococcus, and Proteobacteria [54]. Elovitz and his team conducted a prospective cohort study of 2000 singleton pregnancies to examine the association of cervicovaginal microbiota with spontaneous preterm birth and local immunologic characteristics.…”
Section: Vaginal Microbiota and Spontaneous Preterm Birthmentioning
confidence: 96%
“…The species Lactobacillus mulieris was described in March 2020 from a urine isolate ( 3 ), leading to the subsequent reclassification of numerous Lactobacillus jensenii strains based on average nucleotide identity (ANI) ( 3 , 4 ). L. jensenii and L. mulieris are members of both the urinary and vaginal microbiota ( 4 6 ). More recently , L. mulieris abundance in the vaginal microbiota has been associated with a decreased risk of spontaneous preterm birth ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…L. jensenii and L. mulieris are members of both the urinary and vaginal microbiota ( 4 6 ). More recently , L. mulieris abundance in the vaginal microbiota has been associated with a decreased risk of spontaneous preterm birth ( 5 ).…”
Section: Announcementmentioning
confidence: 99%